The Comparison of Physical Activity Profiles of Elementary School Students in Urban and Rural Areas During COVID-19 Pandemic - Rahmansyah, Fauzi; Budiana, Dian; Stephani, Mesa Rahmi (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
In the midst of COVID-19 pandemic, the role of Physical Education is unseen. The physical activity of the student decreases due to the COVID-19 pandemic. The aim of this research was to find out the differences of physical activity between the elementary school students in urban areas and rural areas during the COVID-19 pandemic. This research used a survey method. The population of the study were elementary school students in urban and rural areas. The subjects of the study were 110 students, 55 students as urban area subjects and 55 students as rural area subjects. The data gained by the researcher were primer data obtained from questionnaires distributed directly. During filling in the questionnaire, the students were assisted and helped by parents. The data were analyzed by the percentage technique. The result of this research concludes that there was a physical activity profiles differences of elementary school students in urban and rural areas during the COVID-19 pandemic. Therefore, the result of the study can be a depiction of physical activity condition during Covid-19 pandemic. The result of the study could inform parents and teachers to pay attention to the moderate physical activity for the students.